Uma cadeia criativa na formação de educadores a partir da proposta curricular do Estado de São Paulo para a disciplina de educação física - Castro, Rosa Cristina Bronzon de (2009)
This piece of research aims at critically understanding the means by which a teacher education project for physical education teachers, within the concept of creative chain (LlBERALI, 2006a e b) can collaborate to implement an officially prescribed material in a public school. The research is carried out in the Citizenship Action Program - phase 2 (PAC-2) context, inserted within Applied Linguistic area and it is founded in the Social-Cultural-Historical Activity Theory (VYGOTSKY, 1934/1998, 1930/2004; lEONTIEV, 1977; ENGESTROM, 1999). In this perspective, the investigation seeks to discuss the concept of "Creative Chain", which encompasses a partnership in which participants intentionally produce "shared meanings"(VYGOTSKY, 1934) in activities that are interconnected in a spiral format (LIBERALI, 2006a e b). Questions pertaining to physical education are also tackled as they are found in official documents and how they are treated by other researchers within the area (BRACHT, 1992; BETTI, 1991, 1998; CAPARROZ, 1997; DAOLIO 2004; KOIYNIAK FILHO, 2008; MELLO, 2006). The adopted methodology is that of the Critical Research of Collaboration (MAGALHÃES, 2007), with its direct intervention in participants' practices so as to create a locus for critical reflection of their actions (MAGALHÃES, 1994/2007, 2003/2007) and to allow for the understanding of the possible transformation (MAGALHÃES, 1998/2007; 2004; LlBERALI,2004; 2006; 2008). In terms of linguistic analyzes and data discussion, the investigation focused on the context of production and the thematic content found through the analysis of lexical choices. Thus, it was possible to understand how the senses and meanings (VYGOTSKY, 1934/2005, 1934/2001) about the contents of an official document were being constructed by the teacher-research participant, by the researcher and by the teacher-supervisor in the planning meetings. Data were produced (by means of audio and video recordings) in a state school in São Paulo which is part of PAC-2. Participants were a physical education teacher of the 5th grade, who has 43 students ranging from 11 to 13 years of age, and the teacher supervisor. Results seem to reveal that the teacher education process developed in activities of the creative chain produce a collaborative space that enable participants to better appropriate the official prescription, without forgetting the needs of the school